Factors Associated With Clinical Recovery After Concussion in Youth Ice Hockey Players. Issue 5 (4th May 2021) - Emery, Carolyn A.; Warriyar KV, Vineetha; Black, Amanda M.; Palacios-Derflingher, Luz; Sick, Stacy; Debert, Chantel; Brooks, Brian L.; Yeates, Keith Owen; Mrazik, Martin; Lebrun, Constance; Hagel, Brent E.; Dukelow, Sean; et al.
Background: The identification of factors associated with clinical recovery in youth after sports-related concussion could improve prognostication regarding return to play (RTP). Purpose: To assess factors associated with clinical recovery after concussion in youth ice hockey players. Study Design: Cohort study; Level of evidence, 2. Methods: Participants were part of a larger longitudinal cohort study (the Safe to Play study; N = 3353). Included were 376 ice hockey players (age range, 11-17 years) from teams in Calgary and Edmonton, Canada, with 425 physician-diagnosed ice hockey–related concussions over 5 seasons (2013-2018). Any player with a suspected concussion was referred to a sports medicine physician for diagnosis, and a Sport Concussion Assessment Tool (SCAT) form was completed. Time to clinical recovery was based on time between concussion and physician clearance to RTP. Two accelerated failure time models were used to estimate days to RTP clearance: model 1 considered symptom severity according to the SCAT3/SCAT5 symptom evaluation score (range, 0-132 points), and model 2 considered responses to individual symptom evaluation items (eg, headache, neck pain, dizziness) of none/mild (0-2 points) versus moderate/severe (3-6 points). Other covariates were time to physician first visit (≤7 and >7 days), age group (11-12, 13-14, and 15-17 years), sex, league type (body checking and no body checking), tandem stance (modified Balance Error Scoring System result ≥4 errors out of 10), and number of previous concussions (0, 1, 2, and ≥3). Results: The complete case analysis (including players without missing covariates) included 329 players (366 diagnosed concussions). The median time to clinical recovery was 18 days. In model 1, longer time to first physician visit (>7 days) (time ratio [TR], 1.637 [95% confidence interval (CI), 1.331-1.996]) and greater symptom severity (TR, 1.016 [95% CI, 1.012-1.020]) were significant predictors of longer clinical recovery. In model 2, longer time to first physician visit (TR, 1.698 [95% CI, 1.399-2.062]), headache (moderate/severe) (TR, 1.319 [95% CI, 1.110-1.568]), and poorer tandem stance (TR, 1.249 [95% CI, 1.052-1.484]) were significant predictors of longer clinical recovery. Conclusion: Medical clearance to RTP was longer for players with >7 days to physician assessment, poorer tandem stance, greater symptom severity, and moderate/severe headache at first visit.